A Novel Composite Material Designed from FeSi Powder and Mn0.8Zn0.2Fe2O4 Ferrite - Magdalena Streckova; Radovan Bures; Maria Faberova; Pavel Kurek; Pavla Roupcova; Hynek Hadraba; Vladimir Girman; Jozef Strecka (Advances in Materials Science and Engineering)
A design of the novel microcomposite material composed of spherical FeSi particles and Mn0.8Zn0.2Fe2O4 ferrite is reported together with a characterization of basic mechanical and electrical properties. The sol-gel autocombustion method was used for a preparation of Mn0.8Zn0.2Fe2O4 ferrite, which has a spinel-type crystal structure as verified by XRD and TEM analysis. The final microcomposite samples were prepared by a combination of the traditional PM compaction technique supplemented with unconventional microwave sintering process of the prepared green compacts. The composition and distribution of the secondary phase formed by the spinel ferrite were examined by SEM. It is demonstrated that the prepared composite material has a tight arrangement without any significant porosity, which manifests itself through superior mechanical properties (high mechanical hardness, Young modulus, and transverse rupture strength) and specific electric resistivity compared to the related composite materials including resin as the organic binder.